DAMPAK STUNTING TERHADAP PRODUKTIVITAS ANAK SEKOLAH DASAR DI KOTA SERANG - Martin Felix; Anna Maria Oktaviani; Hafid Zulbirri (STKIP Subang, 2026)
Stunting is a public health problem with long-term impacts on the quality of human resources, including the productivity of school-age children. In Serang City, stunting prevalence remains a concern despite a decreasing trend in recent years. This study aims to analyze the impact of stunting on the productivity of elementary school children in Serang City by utilizing stunting prevalence data from the Health Office and findings from national and international research published between 2020 and 2025. The research employed a descriptive method based on secondary data analysis and a systematic literature review. The results indicate that stunting negatively affects cognitive abilities, academic achievement, attendance rates, and learning participation among elementary school students. These findings demonstrate that stunting not only influences physical growth but also has direct implications for children’s learning productivity. Therefore, strengthening integrated interventions between the health and education sectors is essential to reduce the impact of stunting and improve the quality of human resources in Serang City. Keywords: stunting, learning productivity, elementary school children, Serang City Abstrak : Stunting merupakan permasalahan kesehatan masyarakat yang berdampak jangka panjang terhadap kualitas sumber daya manusia, termasuk produktivitas anak usia sekolah. Di Kota Serang, prevalensi stunting masih menjadi perhatian meskipun menunjukkan tren penurunan dalam beberapa tahun terakhir. Penelitian ini bertujuan untuk menganalisis dampak stunting terhadap produktivitas anak sekolah dasar di Kota Serang dengan memanfaatkan data prevalensi stunting dari Dinas Kesehatan serta hasil penelitian nasional dan internasional periode 2020–2025. Metode penelitian yang digunakan adalah deskriptif dengan analisis data sekunder dan telaah pustaka sistematis. Hasil penelitian menunjukkan bahwa stunting berpengaruh terhadap kemampuan kognitif, prestasi akademik, tingkat kehadiran, dan partisipasi belajar siswa sekolah dasar. Temuan ini menunjukkan bahwa stunting tidak hanya berdampak pada aspek pertumbuhan fisik, tetapi juga berimplikasi langsung terhadap produktivitas belajar anak. Oleh karena itu, diperlukan penguatan intervensi terintegrasi antara sektor kesehatan dan pendidikan guna menurunkan dampak stunting dan meningkatkan kualitas sumber daya manusia di Kota Serang. Kata kunci : Stunting, Produktivitas Terbatas, Anak Sekolah Dasar, Kota Serang